ADAMTS13 substrate recognition of von Willebrand factor A2 domain. - PRESTON, ROGER (My University, 2006)
ADAMTS13 controls the multimeric size of circulating von Willebrand factor (VWF) by cleaving the Tyr1605?Met1606 bond in theA2 domain. To examine substrate recognition, we expressed in bacteria and purified three A2 (VWF76-(1593?1668), VWF115-(1554?1668), VWFA2-(1473?1668)) and one A2-A3 (VWF115-A3-(1554?1874)) domain fragments. Using high pressure liquid chromatography analysis, the initial rates of VWF115 cleavage by ADAMTS13 at different substrate concentrations were determined, and from this the kinetic constants were derived (Km 1.61 ?m; kcat 0.14 s?1), from which the specificity constant kcat/Km was calculated, 8.70 ? 104 m?1 s?1. Similar values of the specificity constant were obtained for VWF76 and VWF115-A3. To identify residues important for recognition and proteolysis of VWF115, we introduced certain type 2A von Willebrand disease mutations by site-directed mutagenesis. Although most were cleaved normally, one (D1614G) was cleaved ~8-fold slower. Mutagenesis of additional charged residues predicted to be in close proximity to Asp1614on the surface of the A2 domain (R1583A, D1587A, D1614A, E1615A, K1617A, E1638A, E1640A) revealed up to 13-fold reduction in kcat/Km for D1587A, D1614A, E1615A, and K1617A mutants. When introduced into the intact VWFA2 domain, proteolysis of the D1587A, D1614A, and E1615A mutants was also slowed, particularly in the presence of urea. Surface plasmon resonance demonstrated appreciable reduction in binding affinity between ADAMTS13 and VWF115 mutants (KD up to ~1.3 ?m), compared with VWF115 (KD 20 nm). These results demonstrate an important role for Asp1614 and surrounding charged residues in the binding and cleavage of the VWFA2 domain by ADAMTS13.
PUBLISHED
Keywords: Clinical medicine; Hematology; ADAMTS13